Occurrence of Acrylamide in selected Iraqi bakery products and mitigation by partially purified L-Asparaginase (Journal of the College of Basic Education, 2022)
The plenty of scientific evidence on the consequences of dietary acrylamide exposure, justify the requirement to reduce the acrylamide formation in foods. Among the mitigation strategies is the Asparaginase pre – treatment. Therefore, the following study was undertaken to investigate the Acrylamide occurrence in some Iraqi local bakery products as well as using a partially purified Asparaginase for Acrylamide mitigation. After using Ammonium sulfate in Asparaginase precipitation, from Pole beans, the Asparaginase shown to precipitate out at saturation range between 30 – 80 %. In bakery tested samples Acrylamide content were 189.25 – 222.75, 178.75 – 188 and 177.5 – 183.75 µg/Kg for Iraqi traditional Sammoun , Iraqi flat bread and Iraqi bread respectevily. In two samples of biscuit Acrylamide content was 25 and 50 µg/Kg. While no Acrylamide occurrence found to be in other three tested biscuit samples. After adding the crude enzyme and partially purified enzyme to the dough, from Farinograph record, the water absorption values were 58.6% and 59.6% respectively as well as the dough stability time (DST) was 11.5 and 10 min respectively. There were no changes in final loaf properties after enzyme treatment that was confirmed from measuring loaf volume and weight and texture. The addition of crude enzymes and dialyzed partially purified Asparaginase (300 U/kg) to the loaf recipe results in reduction the acrylamide content 39.7% and 42% respectively.